Aqueous solution-processed AlOx dielectrics and their biased radiation response investigated by an on-site technique. (May 2020) - Fang, Yuxiao; Zhao, Chun; Hall, Stephen; Mitrovic, Ivona Z.; Xu, Wangying; Yang, Li; Zhao, Tianshi; Liu, Qihan; Zhao, Cezhou
Abstract: The effect of annealing temperature on the properties of aqueous solution-processed AlOx thin films is reported in this paper. Specifically, the stability of AlOx based Metal Oxide Semiconductor (MOS) capacitor devices under bias-stress (BS) and biased radiation stress (BRS) were assessed by an on-site technique with bias stress time up to 10 5  s. A 662-keV Cs 137 γ-ray radiation source was used, with circa 92 Gy, for biased radiation stress experiments. In order to better understand the origin of degradation mechanisms, the build-up of charge and generation of defects during the BS and BRS were analyzed by calculation of the variation of oxide trap density (ΔNot ) in AlOx bulk and interface trap density (ΔNit ) at the oxide/semiconductor interface. It is been found that high annealing temperature (>250 °C) can result in the formation of AlOx thin films with reduced impurities, low leakage current, and satisfactory BS as well as BRS stability. The results of ΔNot and ΔNit vs stress time indicate that AlOx bulk oxide traps dominate the shift of flat-band voltage (VFB ) under BRS. Furthermore, ΔNot and ΔNit decrease slightly under positive biased radiation stress (PBRS), while the increase in ΔNot and ΔNit concentrations observed under negative biased radiation stress (NBRS), exhibits a mechanism which differs from the traditional two-stage process theory. Highlights: Solution-processed AlOx thin films have satisfied film quality and stability. ΔNit can be attributed to trapping/de-trapping behavior among AlOx . ΔNot is ascribed to the passivation/de-passivation of Si/AlOx interface. Oxide trapped charges dominant the shift of VFB .